2013 IEEE 12th International Symposium on Network Computing and Applications 2013
DOI: 10.1109/nca.2013.24
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Rate Adaptation Into Green Networking for Future Data Centers

Abstract: Despite some proposals for energy-efficient topologies, most of the studies for saving energy in data center networks are focused on traffic engineering, i.e., consolidating flows and switching off unnecessary network devices. The major weakness of this approach is network oscillation brought by the frequent change of network topology when traffic fluctuates very fast. In this paper, we propose to incorporate rate adaptation into green data center networks. With rate adaptive network devices, we aim at approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Techniques exploiting rate adaptation are explored for data centre networks in [21,22]. Complementary to these works, we focus on the energy consumption from the perspective of software application, including not only the NICs, but also the other components involved in network transfers.…”
Section: Related Workmentioning
confidence: 99%
“…Techniques exploiting rate adaptation are explored for data centre networks in [21,22]. Complementary to these works, we focus on the energy consumption from the perspective of software application, including not only the NICs, but also the other components involved in network transfers.…”
Section: Related Workmentioning
confidence: 99%
“…Generally there are two types of network virtualization environment model. [12], [11]. This refers as several virtual networks from different service providers coexist together over the part of fully of the existing physical network provided by the infrastructure providers.…”
Section: Virtual Architecturementioning
confidence: 99%
“…Fig. 3 shows the example to tow co-existing Virtual Networks.Recursion: When one or more Virtual networks are spawned form another Virtual network hierarchy with parent-child relationships, it is known as recursion as well as nesting of virtual networks [11]. The Re-visitation allows a physical node to host multiple virtual node of a single virtual network.…”
Section: Virtual Architecturementioning
confidence: 99%
“…Then, to achieve energy conservation, they reduce the number of needed active switches that balance traffic flows, depending on the relationship between power consumption and routing. In [22], authors showed the benefit of using link rate adaptation in a datacenter network. The objective is to find the rates of the different links that minimize the energy consumption of the whole network.…”
Section: A Energy Reduction In Wired Networkmentioning
confidence: 99%